Research and Optimization of Liquid Cooling Plate for High-heat-flux Components - Zhan Binfei; Xu Hongbo; Zhang Hainan; Leng Dongmei; Tian Changqing; Zhou Yuan (Zhileng xuebao)
Fluid cooling plates are widely used in the heat dissipation of high-density components, which imposes stricter requirements for the temperature uniformity of the plate surface. In this study, to improve the temperature uniformity of the liquid-cooled plate, a liquid-cooled plate with a single inlet and single outlet was designed. Under a load of 300 W, the average temperature uniformities of the plate cooled by a single-phase water and multiple-phase-change working medium were evaluated to be within 2 ℃ and 2.6 ℃ (R236fa), respectively. To further improve the temperature uniformity, a scheme of a single inlet and multiple outlets for optimizing the flow channel was proposed. The effectiveness of the optimization scheme was verified by a simulation and experiment. The average temperature uniformity of the plate surface cooling with the R236fa working medium can be controlled to be within 2 ℃ after the optimization.